(untitled) (Asian-Australasian Journal of Food Safety and Security, 2026)
Mucuna seeds, once largely neglected, are gradually being incorporated into the diets of some communities in Benin because of their high protein content. However, their utilization is constrained by the presence of antinutritional compounds, particularly L-Dopa, which may pose health risks if not adequately reduced during processing. Traditional processors employ various processing methods to detoxify the seeds, but the safety of the resulting foods prepared from different Mucuna varieties has not been fully established. This study aimed to evaluate the L-Dopa and tannin contents of the major traditional Mucuna-based foods in Benin in relation to their processing methods. A total of 84 processors and consumers were interviewed to document Mucuna processing practices and consumption patterns. Subsequently, 10 Mucuna-based food samples were collected and analysed for L-Dopa using the USP–NF 2022, Issue 1 method, while total tannins were determined using the Folin–Ciocalteu method. The results showed that Mucuna processing and consumption were infrequent, occurring mainly once per quarter, with Ata, Afitin, and Abobo being the principal traditional products. Raw white- and black-seeded Mucuna contained 4.6% and 5.0% L-Dopa, respectively. Following processing, L-Dopa contents decreased markedly, ranging from 0.002% to 3.0% depending on the product. Abobo and Afitin contained residual L-Dopa levels below the 1.0% safety threshold, whereas Ata exceeded this limit. Tannin contents in processed products ranged from 0.033 to 0.841 mg tannic acid equivalents/g, indicating substantial reductions following soaking, cooking with water renewal, roasting, and fermentation. Overall, traditional processing methods effectively ensured the safety of Abobo and Afitin, whereas further optimization is required for Ata. These findings provide evidence-based guidance for improving traditional Mucuna processing practices and support the safe utilization of this underutilized legume to enhance dietary diversification and household food security in Benin and similar settings. Asian Australas. J. Food Saf. Secur. 2026, 10(2), 64-76